A Giant Urethral Stone With Urethrocutaneous Fistula: A Case Report - Ikhwan, Haznur; Rizaldi, Aril (ANATOMICA MEDICAL JOURNAL | AMJ, 2023)
Urethral stones are commonly associated with urinary tract calculi and underlying   diverticulum   or   stricture urethra. Urethral calculus represent less then 1%  of all urinary stones diseases. Giant urethral calculi frequently may occur in male and rarely in female. This purpose of reporting this case is to describe a way to diagnose urethral stone cases and so that patients can be treated by urologists. CASE PRESENTATION: A 48-year-old man patient with a giant urethral stone with urethrocutaneous fistula for the past 1 year and a diventral penile meatotomy was performed. With physical examination found on the penis palpable stone +/- 4cm anterior to the penis, the tip of the stone can be seen from Eksternum Urethra Orifice. There was also a urethrocutaneous fistula on the ventral penis, about a stone, measuring +/- 0.1 cm so a diventral penis meatotomy was performed, a stone measuring 4x1 cm was found, with unhealthy tissue in the urethra along the stone. DISCUSSION: The incidence of penile urethral stones is increasing which may due to various factors especially climate change and genetic factors. The gradual formation of this long penile urethral stone could take approximately around 5-10 years which indicates the patient’s persistent ignorance of pain and discomfort in the urinary tract. In our case, 3 months after the first operation, urethrocutaneous fistula repair was performed. Evaluation after 2 months after fistula repair, Urination is smooth, no pain, good wound, no fistula, was performed in our report. CONCLUSION: From our experience some predisposing factors of urethral stone with a Urethrocutaneous fistula. The complications seriously affect the quality of life and even cause more serious consequences, so physicians and patients should be aware.Keywords: giant urethral stone, urethrocutaneous fistula, meatotomi ventral penis